THE IMPACT OF DIGITAL TRANSFORMATION ON GLOBAL BRANDING AND CUSTOMER SERVICE: A STUDY OF ZARA FASHION - Musty, Bertha; Lestari, Elisa Diana; Rifani, Hasnatia; Santika, Vanya Zahwa; Susilawati Sugiana, Neng Susi (Jurnal Komputer Bisnis, 2025)
Digital transformation has become a key driver in shaping branding and customer service strategies within the global fast fashion industry, with Zara standing out as a leading example. This study investigates how the adoption of digital technologies—such as artificial intelligence (AI), big data, social media, and omnichannel platforms—enhances global brand identity and improves the quality of customer service. Employing a mixed-methods approach, the research analyzes Zara’s digital strategy alongside consumer perceptions of brand experience in the digital age. The findings reveal that digital technologies enable personalization, two-way communication, and brand consistency across diverse international markets. Furthermore, digitalization contributes to greater operational efficiency and stronger customer engagement, leading to increased customer satisfaction and loyalty. These results offer practical insights for fashion companies seeking to stay competitive and relevant amid the ongoing digital transformation of consumer behavior, while also contributing to the theoretical understanding of the relationship between digital transformation, global consumer behavior, and brand strength.